A Narrative of Different Voices: Stylistic Analysis of Multiple Points of View in Zadie Smith’s “NW” - Krasniqi, Lurjana; Tahiri, Lindita (Respectus Philologicus, 2022)
While the post-colonial approach (Fernández Carbajal, 2016; López-Ropero, 2016) has dominated research on Zadie Smith’s postmodern work, NW (2013), there has been little to no stylistic analysis of the novel. The article aims to fill in this theoretical gap by examining the different modes of point of view, indicating how they are linguistically encoded. Using Leech and Short’s model of narratological aspects of viewpoint (2007), the stylistic features of the third-person narrator and the reflectors are revealed. The analysis seeks to demonstrate that the narrative style varies with each shift of perspective and that the voice of the narrator and the characters’ points of view are linguistically intertwined. The research points out the stylistic metamorphosis of the narrator who moves from mimetic storytelling to metafiction, alternating between the covert narrator who foregrounds the characters’ point of view and the overt one who constantly pinpoints the linguistic identity of the novel. The fusion of form and content becomes the storyline of this novel, where the differences between viewpoints of the narrating voices reflect the differences between their lives.